Metabolic Effects of Sodium Thiosulfate During Resuscitation from Trauma and Hemorrhage in Cigarette-Smoke-Exposed Cystathionine-γ-Lyase Knockout Mice - Maximilian Feth; Felix Hezel; Michael Gröger; Melanie Hogg; Fabian Zink; Sandra Kress; Andrea Hoffmann; Enrico Calzia; Ulrich Wachter; Peter Radermacher; Tamara Merz (Biomedicines)
Background: Acute and chronic pre-traumatic cigarette smoke exposure increases morbidity and mortality after trauma and hemorrhage. In mice with a genetic deletion of the H2S-producing enzyme cystathione-γ-lyase (CSE−/−), providing exogenous H2S using sodium thiosulfate (Na2S2O3) improved organ function after chest trauma and hemorrhagic shock. Therefore, we evaluated the effect of Na2S2O3 during resuscitation from blunt chest trauma and hemorrhagic shock on CSE−/− mice with pre-traumatic cigarette smoke (CS) exposure. Since H2S is well established as being able to modify energy metabolism, a specific focus was placed on whole-body metabolic pathways and mitochondrial respiratory activity. Methods: Following CS exposure, the CSE−/− mice underwent anesthesia, surgical instrumentation, blunt chest trauma, hemorrhagic shock for over 1 h (target mean arterial pressure (MAP) ≈ 35 ± 5 mmHg), and resuscitation for up to 8 h comprising lung-protective mechanical ventilation, the re-transfusion of shed blood, fluid resuscitation, and continuous i.v. noradrenaline (NoA) to maintain an MAP ≥ 55 mmHg. At the start of the resuscitation, the mice randomly received either i.v. Na2S2O3 (0.45 mg/gbodyweight; n = 14) or the vehicle (NaCl 0.9%; n = 11). In addition to the hemodynamics, lung mechanics, gas exchange, acid–base status, and organ function, we quantified the parameters of carbohydrate, lipid, and protein metabolism using a primed continuous infusion of stable, non-radioactive, isotope-labeled substrates (gas chromatography/mass spectrometry) and the post-mortem tissue mitochondrial respiratory activity (“high-resolution respirometry”). Results: While the hemodynamics and NoA infusion rates did not differ, Na2S2O3 was associated with a trend towards lower static lung compliance (p = 0.071) and arterial PO2 (p = 0.089) at the end of the experiment. The direct, aerobic glucose oxidation rate was higher (p = 0.041) in the Na2S2O3-treated mice, which resulted in lower glycemia levels (p = 0.050) and a higher whole-body CO2 production rate (p = 0.065). The mitochondrial respiration in the heart, kidney, and liver tissue did not differ. While the kidney function was comparable, the Na2S2O3-treated mice showed a trend towards a shorter survival time (p = 0.068). Conclusions: During resuscitation from blunt chest trauma and hemorrhagic shock in CSE−/− mice with pre-traumatic CS exposure, Na2S2O3 was associated with increased direct, aerobic glucose oxidation, suggesting a switch in energy metabolism towards preferential carbohydrate utilization. Nevertheless, treatment with Na2S2O3 coincided with a trend towards worsened lung mechanics and gas exchange, and, ultimately, shorter survival.